Quantitative Relationship Between Solar Radiation and Grain Filling Parameters of Maize - Yang, Yunshan; Liu, Guangzhou; Guo, Xiaoxia; Liu, Wanmao; Xue, Jun; Ming, Bo; Xie, Ruizhi; Wang, Keru; Hou, Peng; Li, Shaokun (Frontiers in Plant Science, 2022)
A quantitative understanding of the factors driving changes in grain filling is essential for effective prioritization of increasing maize yield. Grain filling is a significant stage in maize yield formation. Solar radiation is the energy source for grain filling, which is the ultimate driving factor for final grain weight and grain filling capacity that determine maize yield. Here, we first confirmed the quantitative relationships between grain filling parameters and photosynthetically active radiation (PAR) by conducting field experiments using different shading and plant density conditions and cultivars in 2019 and 2020 in Xinjiang, China. The results showed that with every 100 MJ m−2 increase in PAR, the average grain filling rate (Gave), maximum grain-filling rate (Gmax), and the kernel weight at the time of maximum grain-filling rate (Wmax) increased by 0.073 mg kernel−1 day−1, 0.23 mg kernel−1 day−1, and 0.24 mg kernel−1, and the time of maximum grain-filling rate (Tmax) delayed by 0.91 day. Relative changes in PAR were significantly and positively correlated with relative changes in yield and Gave. With every 1% change in PAR, yield and Gave changed by 1.16 and 0.17%, respectively. From the perspective of grain filling capacity, DH618 was a more shade-resistant cultivar than XY335 and ZD958. It is urgent to breed maize cultivars with low light tolerance and high grain yield in the face of climate change, particularly the decrease in solar radiation.